From Molecules to Amoeboid Movement: A New Way for Understanding the Morphology Through Actin-Binding Proteins - Ekaterina Volkova; Igor Pozdnyakov; Mikhail Petukhov; Valeriia Polezhaeva (Biomolecules)
Amoebozoa is a group of single-celled organisms that change their shape during locomotion. However, there is a taxon-specific complex of morphological characters inherent in the moving amoebae, known as locomotive forms. Actin is one of the proteins most important for amoeboid movement that, together with actin-binding proteins, construct the architecture of the cytoskeleton in the amoeboid cells. One of the actin-binding proteins is the Arp2/3 complex that provides a connection between actin filaments at an angle of 70°. In this paper, we predicted 3D models of bonded subunits Arp2 and Arp3 for 30 species from different taxa of Amoebozoa based on the publicly available transcriptomic data. Moreover, we predicted the binding free energy (ΔG) of bonded subunits Arp2 and Arp3 for 30 species and tried to link it to the morphology of the locomotive forms of amoebae. The ΔG values are the lowest in amoebae with the broad hyaline area, like Vannella spp. Amoebae that produce thin hyaline projections, like Vexillifera abyssalis, are characterized by intermediate ΔG values. Finally, the highest ΔG values are typical for the group of amoebae that have no conspicuous hyaline areas of the cytoplasm, like Pelomyxa shiedti, or have small hyaline caps, like Arcella intermedia. The presented analysis provides new insights into the molecular mechanisms of shape formation in amoeboid cells.